2019
DOI: 10.1177/1363459319831331
|View full text |Cite
|
Sign up to set email alerts
|

Where to find accurate information on attention-deficit hyperactivity disorder? A study of scientific distortions among French websites, newspapers, and television programs

Abstract: Attention-deficit/hyperactivity disorder is the most frequent mental disorder among school-age children. This condition has given rise to a large mediatic coverage, which contributed to the shaping of the lay public’s perceptions. We therefore conducted two studies on the way attention-deficit/hyperactivity disorder was portrayed in the TV programs and the lay-public press in France between 1995 and 2015, but the growing part played by the Internet required an additional study to analyze and compare the scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Since the beginning of the 2000s, television programs and websites dedicated to ADHD have proliferated in France. The vast majority of them support an organic cause for ADHD and present the drug treatment in an excessively favorable light ( 71 , 72 ). The print media have also helped to raise awareness of ADHD but have been more nuanced about the use of MPH ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the 2000s, television programs and websites dedicated to ADHD have proliferated in France. The vast majority of them support an organic cause for ADHD and present the drug treatment in an excessively favorable light ( 71 , 72 ). The print media have also helped to raise awareness of ADHD but have been more nuanced about the use of MPH ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Controversies remain despite what some studies may suggest, which are too affirmative, so that a strictly and exclusively biological approach to psychiatry may appear as a speculative bubble ( Gonon, 2011 ). The question of referring to reliable information arises in a major way, as in the example of attention deficit hyperactivity disorder (ADHD) ( Ponnou et al, 2019 ). What if mental disorders are not just brain disorders?…”
Section: New Orientations In Psychopathology In a Digital Contextmentioning
confidence: 99%
“…For the most part, previous studies on media coverage of AD/HD diagnosis and treatment have been quantitative and descriptive, and hence largely under theorized (see however Schmitz et al, 2003 who discuss media representations of AD/HD in relation to social representations theory). Examples of such studies include Börjesson (1999), Cassels et al (2003), Williams et al (2008), Horton-Salway (2011, 2013), Isaksen and Tjora (2016), Ponnou and Gonon (2017), and Ponnou et al (2020). A common theme that can be identified is that the biomedical model of AD/HD, in various ways, frequently dominates the media space.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ponnou and Gonon (2017) show that for the most part news coverage of AD/HD promotes a favorable representation of the treatment and diagnosis. Ponnou et al (2020) performed a quantitative study of website coverage and tv programs focusing on AD/HD and found that it was portrayed as an essentially biomedical concept. Clarke’s (2011) investigation of popular magazines, however, shows that there is a more polarized portrayal of AD/HD, and whether the associated behaviors constitute a medical problem or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation